Preparation, characterization and antitumor activity evaluation of apigenin nanoparticles by the liquid antisolvent precipitation technique - Weiwei Wu; Yuangang Zu; Li Wang; Lingling Wang; Huimei Wang; Yuanyuan Li; Mingfang Wu; Xiuhua Zhao; Yujie Fu (Taylor & Francis Group, 2017)
The present work aimed to apply the liquid antisolvent precipitation (LAP) method for preparing the apigenin nanoparticles and thereby improving the solubility and bioavailability of apigenin. The different experimental parameters on particle size were optimized through central composite design (CCD) using the Design-Expert® software. Under the optimum conditions, the particle size of the apigenin nanosuspension was about 159.2 nm. In order to get apigenin nanoparticles, the freeze-drying method was selected and the mannitol was used as a cryoprotectant. Then the solid state properties of the apigenin nanoparticles were investigated using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermo gravimetric (TG), and X-ray diffraction (XRD). The results obtained displayed that the apigenin nanoparticles exhibited near-spherical shape and could be transformed into an amorphous form. In addition, the dissolving test, the bioavailability in rats, and the antitumor activity were also studied. The experimental results showed that the solubility of the apigenin nanoparticles were about 29.61 times and 64.81 times of raw apigenin in artificial gastric juice and in artificial intestinal juice, respectively, and the apigenin nanoparticles showed higher dissolution rates compared to raw apigenin, and was about 6.08 times and 6.14 times than that of raw apigenin in artificial gastric juice and in artificial intestinal juice. The oral bioavailability of apigenin nanoparticles was about 4.96 times higher than that of the raw apigenin, but the apigenin nanoparticles had no toxic effect on the organs of rats. In addition, the apigenin nanoparticles had a higher inhibition to HepG2 cells by lower IC50 than that of raw apigenin.